FUNDAMENTAL STOCK INVESTMENT DECISION MAKING WITH PRICE EARNING RATIO (PER) APPROACH IN TECHNOLOGY SUBSECTOR STOCK LISTED ON THE INDONESIA STOCK EXCHANGE - Hasvinsa Mahra; Chairil Akhyar; Marzuki; Wardhiah (PT. Radja Intercontinental Publishing, 2023)
This study aims to determine fundamental investment decisions with the Price Earning Ratio (PER) approach in technology subsector stocks listed on the Indonesia Stock Exchange for the 2018-2021 period. This study uses secondary data in the form of financial statements of each technology subsector company, where the sample used in this study is as many as 11 technology subsector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The data analysis method used in this study is fundamental analysis using the Price Earning Ratio (PER) approach with the help of Microsoft Excel 2021 software. The results showed that all technology subsector companies used in this study were correctly valued because the intrinsic value of the stock was equal to the stock market price or experienced price stability so that investors could hold the stock.